Behavioral health policy for improving population health and wellbeing: opportunities for investment in evidence-based policymaking. Issue 3 (7th August 2020) - Crowley, Max; Green, Lawrie; Scott, Taylor; Long, Elizabeth
Abstract: The high cost of behavioral health problems across the population continues to highlight the need to integrate high-quality behavioral interventions across a variety of service settings. To successfully achieve such a system-wide transformation will require supporting federal policies that invest in sustainable high-quality services. To support these efforts we provide a mixed-method study of all federal mental health legislation over the last three decades. Results indicate that mental and behavioral health policies have grown. Further, specific characteristics that comprise bills that are successfully enacted into law are identified. Finally, opportunities for the field to engage with policymakers to support widespread integration of behavioral health services are offered.